2019
DOI: 10.3389/fmicb.2019.00660
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Pomegranate Peel Extract and Probiotics on Pre-adipocyte Differentiation

Abstract: The beneficial effects of pomegranate are due to the ellagitannins and anthocyanins content, which are protective toward a wide variety of diseases including inflammatory diseases. Many investigators have reported that pomegranate waste (peel and seeds) extracts, made from waste product of industrial processing, show free radical scavenger and a potent antioxidant capacity. Pomegranate extracts (PEs) were also reported to possess noteworty antibacterial, antiviral, hypolipidemic, and anti-inflammatory bioactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 54 publications
0
50
0
Order By: Relevance
“…Polysaccharides extracted from pomegranate peels are known to possess excellent antioxidant and immunomodulatory properties [59]. Joseph and colleagues [60] demonstrated that a galactomannan extracted from the peel of Punica granatum L. fruit presents radical scavenging activity [61] and prebiotic effects, stimulating the growth of beneficial bacteria in the colon and maintaining a good state of health of the intestine [62]. In a dextran-sulfate-induced colitis animal model, Yue and colleagues [63] showed that the polysaccharides ameliorated the inflammatory response through lowering TNF-α, IL-1β, IL-6, and MPO activity and increased AMPK activity.…”
Section: Discussionmentioning
confidence: 99%
“…Polysaccharides extracted from pomegranate peels are known to possess excellent antioxidant and immunomodulatory properties [59]. Joseph and colleagues [60] demonstrated that a galactomannan extracted from the peel of Punica granatum L. fruit presents radical scavenging activity [61] and prebiotic effects, stimulating the growth of beneficial bacteria in the colon and maintaining a good state of health of the intestine [62]. In a dextran-sulfate-induced colitis animal model, Yue and colleagues [63] showed that the polysaccharides ameliorated the inflammatory response through lowering TNF-α, IL-1β, IL-6, and MPO activity and increased AMPK activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the pomegranate extract could decrease the level of lipids in the blood with significant anti-inflammatory activities. Recent in vitro study has also demonstrated that the polyphenols contained in pomegranate extracts in combination with probiotics induces synergistic effects that substantially reduces the triglyceride levels and intracellular lipid increase ( Sorrenti et al., 2019 ). The study showed that in vitro treatment with pomegranate extract and probiotics improved the expression of fatty acid synthase, adiponectin, adipogenic markers, PPARγ and SREBP, as well as inflammatory cytokine, IL-6.…”
Section: Antioxidants In Ameliorating Obesity and Associated Comorbidmentioning
confidence: 99%
“…While a number of recent studies explored the interactions between natural products and antifungal drugs (Shin, 2003; Shin and Kang, 2003; Shin and Lim, 2004; Karioti et al, 2011), the use of such combined antifungal treatments in agricultural setting remains limited, particularly when compared to clinical applications. Pomegranate by-products, such as peel and seeds, are considered a rich source of bioactive compounds such as flavonoids, phenolic acids, and tannins which have free radical scavenging activity and antioxidant capacity (Panichayupakaranant et al, 2010; Sorrenti et al, 2019). Several studies have been reported on the effectiveness of pomegranate peel extracts (PPEs) against human and plant fungal pathogens (Dikmen et al, 2011; Glazer et al, 2012; Foss et al, 2014; Pangallo et al, 2017; Rosas-Burgos et al, 2017).…”
Section: Introductionmentioning
confidence: 99%